How we die : reflections on life's final chapter - Nuland, Sherwin B., 1930-2014 (Vintage, 1995)
Presents a meditation and portrait of the experience of dying that elucidates the decisions that can be made to allow each person an understanding of death, as well as his or her own choice of death
Obsahuje rejstřík
Keywords: smrt; umírání; tanatologie; death; dying; thanatology; monografie; monographs